If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (Y + 4)(y + -1) + -14 = 0 Reorder the terms: (4 + Y)(y + -1) + -14 = 0 Reorder the terms: (4 + Y)(-1 + y) + -14 = 0 Multiply (4 + Y) * (-1 + y) (4(-1 + y) + Y(-1 + y)) + -14 = 0 ((-1 * 4 + y * 4) + Y(-1 + y)) + -14 = 0 ((-4 + 4y) + Y(-1 + y)) + -14 = 0 (-4 + 4y + (-1 * Y + y * Y)) + -14 = 0 (-4 + 4y + (-1Y + yY)) + -14 = 0 Reorder the terms: (-4 + -1Y + 4y + yY) + -14 = 0 (-4 + -1Y + 4y + yY) + -14 = 0 Reorder the terms: -4 + -14 + -1Y + 4y + yY = 0 Combine like terms: -4 + -14 = -18 -18 + -1Y + 4y + yY = 0 Solving -18 + -1Y + 4y + yY = 0 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '18' to each side of the equation. -18 + -1Y + 4y + 18 + yY = 0 + 18 Reorder the terms: -18 + 18 + -1Y + 4y + yY = 0 + 18 Combine like terms: -18 + 18 = 0 0 + -1Y + 4y + yY = 0 + 18 -1Y + 4y + yY = 0 + 18 Combine like terms: 0 + 18 = 18 -1Y + 4y + yY = 18 Add '-4y' to each side of the equation. -1Y + 4y + -4y + yY = 18 + -4y Combine like terms: 4y + -4y = 0 -1Y + 0 + yY = 18 + -4y -1Y + yY = 18 + -4y Reorder the terms: -18 + -1Y + 4y + yY = 18 + -4y + -18 + 4y Reorder the terms: -18 + -1Y + 4y + yY = 18 + -18 + -4y + 4y Combine like terms: 18 + -18 = 0 -18 + -1Y + 4y + yY = 0 + -4y + 4y -18 + -1Y + 4y + yY = -4y + 4y Combine like terms: -4y + 4y = 0 -18 + -1Y + 4y + yY = 0 The solution to this equation could not be determined.
| X^3y^5x^5= | | 2lg(k)-4=0 | | 4.25x-4.0x=2 | | 2logk-4=0 | | 4.25x-3.65x=4 | | 4-4*5+3=-13 | | 4-(2y)=12 | | =4-4*5+3 | | 4.0x+2=3.65x+4 | | 7*(5x+2)+9=58 | | 7x+15-2x=8+4x-2 | | 0.2x-0.1=1 | | t^3=196t | | 5y^5+45y^5=30y^4 | | 4.50x-4.0x=2 | | 4.50x-3.75x=4 | | logs(6x-8)=2 | | 3b/a^-5/7 | | x^2+14x=100 | | 4.0x=3.75x+4 | | 10+2(x)=30 | | x^4-676x^2=0 | | b-10+b+10=180 | | 5(x-2)+11=36 | | 216/ | | 4.45x-4.0x=2 | | F(x)=7x^2+5x+1 | | 35x/7y | | 4.45x-3.75x=4 | | X-0.1x=-26.4 | | x+2x+70=180 | | 0.4x+x=28 |